On Extremal Problems in Certain New Bergman Type Spaces in Some Bounded Domains in Cn - Romi F. Shamoyan; Olivera Mihić (Journal of Function Spaces)
Based on recent results on boundedness of Bergman projection with positive Bergman kernel in analytic spaces in various types of domains in Cn, we extend our previous sharp results on distances obtained for analytic Bergman type spaces in unit disk to some new Bergman type spaces in Lie ball, bounded symmetric domains of tube type, Siegel domains, and minimal bounded homogeneous domains.